2017
DOI: 10.1007/s11947-017-2041-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Power Coupled with Hot Air Drying on Sorption Isotherms and Microstructure of Orange Peel

Abstract: Drying is one of the most cost-effective methods of worthwhile by-product valorisation. This study had two main objectives. The first was to determine the effect of hot air drying (HAD) combined with microwave (MW) irradiation on the treatment kinetics and the macrostructural and microstructural properties of the dried product. The second aim was to develop engineering tools to predict the extent of dehydration. Drying was performed using hot air at 55 ºC and the combined (HAD + MW) treatment at different powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Microwave drying is fast becoming popular. Several researchers have used this method to process banana peels [ 93 , 94 ], orange peels [ 95 , 96 ], lemon peels [ 97 ], papaya peels [ 98 ], pitaya peels [ 99 ], and pomegranate peel waste [ 86 , 88 , 89 ], to name a few. For pomegranate peel processing using microwave drying, the study by Calín-Sánchez et al [ 88 ] on cultivar Mollar de Elche showed that vacuum microwave drying at 240 W provided better results, giving punicalagin isomer contents (α- and β-PC) of 85.6 and 74.6 mg/g of DW, respectively, compared to convective predrying and other microwave drying levels studied ( Table 4 ).…”
Section: Effects Of Drying Methodsmentioning
confidence: 99%
“…Microwave drying is fast becoming popular. Several researchers have used this method to process banana peels [ 93 , 94 ], orange peels [ 95 , 96 ], lemon peels [ 97 ], papaya peels [ 98 ], pitaya peels [ 99 ], and pomegranate peel waste [ 86 , 88 , 89 ], to name a few. For pomegranate peel processing using microwave drying, the study by Calín-Sánchez et al [ 88 ] on cultivar Mollar de Elche showed that vacuum microwave drying at 240 W provided better results, giving punicalagin isomer contents (α- and β-PC) of 85.6 and 74.6 mg/g of DW, respectively, compared to convective predrying and other microwave drying levels studied ( Table 4 ).…”
Section: Effects Of Drying Methodsmentioning
confidence: 99%
“…Therefore, the moisture removal of drying materials is affected by the interaction of hot air and microwave in the MWHA drying process. In the past few years, some studies using the combination of hot air and microwave have been reported for drying food products including soybean [19], potato [20], longan [21], and orange peel [22]. However, up to date, no report has been found on the drying of Chinese yam using MWHA.…”
Section: Introductionmentioning
confidence: 99%
“…Although viscosity of both treatments showed similar values [3], the higher swelling capacity of HAD + MW treated fiber provoked a significant decrease in the viscoelasticity of the samples. An increase in particle size due to an increase in porosity during drying [4], improved fiber swelling capacity ( Fig. 4).…”
Section: Fig 3 Dielectric Isotherm At 20 Ghz Of Orange Peel Treated mentioning
confidence: 97%